Health impacts of seated arm ergometry training in patients with a diabetic foot ulcer: protocol for a randomised controlled trial. Issue 6 (21st June 2020) - McCarthy, Matthew; Yates, Thomas; Webb, David; Game, Frances; Gray, Laura; Davies, Melanie J
Abstract : Introduction: Once diagnosed with a diabetic foot ulcer (DFU), patients are advised to offload, keeping pressure off the foot in order to facilitate ulcer healing. An increase in offloading is often accompanied by reductions in physical activity which can worsen the overall health of patients. While unable to perform traditional forms of upright activity, one mode of exercise that would allow patients to be physically active while adhering to offloading instruction is seated arm ergometry. The merits of tailored aerobic exercise in DFU remain unexplored. Methods and analysis: This is a prospective open-label randomised controlled trial. Participants will be randomised to one of two groups, an exercise intervention group or control. The intervention group are required to undertake arm ergometry training at a moderate intensity (65%–75% HRpeak), three times per week for 12 weeks as individually prescribed by an exercise physiologist, while the control group will continue to receive standard care alone. Assessment of outcome measures will occur at baseline and after the intervention period, these will include: a seated VO2 peak test, a blood sample, a short physical performance battery, a dual-energy X-ray absorptiometry scan and completing a range of health-based questionnaires. The above will be used to determine: cardiorespiratory fitness, metabolic health, physical function, body composition and quality of life, respectively. Ulcer area will also be measured as an approximate marker of ulcer healing. Ethics and dissemination: This trial has been approved by 'Yorkshire & The Humber—Leeds West Research Ethics Committee' (19/YH/0269). Trial results will be published in peer-reviewed journals and through conference presentations. Trial registration number: ISRCTN16000053 . Registered in accordance with WHO Trial Registration Data Set (version 1.3.1).